1996
DOI: 10.1177/030098589603300306
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of Acute Inhaled Lethal Ricin Intoxication in Rhesus Monkeys

Abstract: Abstract. Five unimmunized adult rhesus monkeys weighing 5.9-6.3 kg were challenged with a precalculated, inhaled dose of 20.95-41.8 &kg of aerosolized ricin. Two males and three females either died or were killed at the onset of respiratory distress between 36 and 48 hours post-ricin inhalation and were necropsied. Consistent gross and microscopic lesions were confined to the thoracic cavity. All monkeys had multifocal to coalescing fibrinopurulent pneumonia, diffuse necrosis, and acute inflammation of airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 13 publications
5
87
2
3
Order By: Relevance
“…4d). The histological lesions observed in these mice are consistent with an aerosolized ricin exposure, and generally represent the temporal progression of acute pulmonary toxicity described in other animals exposed to ricin via aerosol (Poli et al, 1996;Wilhelmsen and Pitt, 1996).…”
Section: Histopathologic Changes In the Lungssupporting
confidence: 73%
See 1 more Smart Citation
“…4d). The histological lesions observed in these mice are consistent with an aerosolized ricin exposure, and generally represent the temporal progression of acute pulmonary toxicity described in other animals exposed to ricin via aerosol (Poli et al, 1996;Wilhelmsen and Pitt, 1996).…”
Section: Histopathologic Changes In the Lungssupporting
confidence: 73%
“…5a). Another physiological parameter monitored was the total body weight loss; it is known that ricin intoxicated animals suffer from significant weight loss (Wilhelmsen and Pitt, 1996). Indeed, a reduction of approximately 25% of the original weight was observed for BALB/c mice that inhaled ricin by 192 h. The mice that received the saline treatment maintained their original body weight and appeared to be healthy throughout the observation period (Fig.…”
Section: Physiological Changes In the Lungs Due To Ricin Toxicitymentioning
confidence: 99%
“…These data are consistent with previous reports on the histopathological effects of aerosolized ricin in animal systems. 20,21,[31][32][33] In addition, we have demonstrated that instilled ricin caused widespread nuclear localization of phosphorylated ERK, p38 MAPK, and JNK, but only phosphorylated p38 MAPK was evident in control lungs. These results are consistent with data obtained by immunoblotting, which demonstrated that ricin induced a large increase in phosphorylated JNK and ERK, but not p38 MAPK (Figure 3a).…”
Section: Discussionmentioning
confidence: 66%
“…Animals were infected by aerosol at the U.S. Army Medical Research Institute of Infectious Diseases by using a nose-only system where aerosols are generated in a class III biosafety glove box cabinet under negative pressure or in a completely contained biosafety level 4 air-locked area. The biosafety level 3 exposure chamber was a 16-liter Plexiglas box with one side containing a circular latex dam with a cutout into which the nose and mouth of the rabbit were inserted (41). The aerosol was generated with a Collison nebulizer containing bacilli suspended in the 10% dilution of oleic albumin complex.…”
Section: Methodsmentioning
confidence: 99%